The Effect of Leadership and Family Business Experience on Social Entrepreneurial Intentions: The Role of Self-Efficacy and Entrepreneurial Attitudes - Sriwahyuni, Sriwahyuni; Kurjono, Kurjono (Dinamika Pendidikan, 2023)
This research aims to examine the effect of leadership and family business experience on social entrepreneurial intentions which are mediated by self-efficacy and moderated by entrepreneurial attitudes in Accounting Education study program students in Indonesia. Determination of the sample size was carried out using the purposive sampling method using the Isaac and Michael formula. The total number of samples from this research was 366 respondents consisting of students from the Accounting Education study program. The data collection technique used was a questionnaire. The data analysis method used is Structural Equation Model-Partial Least Square using the SmartPLS 3.0 application. The research results reveal that leadership and family business experience have a positive  on self-efficacy. Furthermore, leadership and self-efficacy have a positive  on social entrepreneurial intentions, while family business experience has no direct  on social entrepreneurial intentions. Self-efficacy significantly mediates the effect of family business experience on social entrepreneurial intentions. Then entrepreneurial attitude significantly moderates the effect of self-efficacy on social entrepreneurial intentions. In connection with the mediating role of self-efficacy in the effect of family business experience on entrepreneurial intentions, it is necessary to increase student involvement in managing family businesses so that they can instill an entrepreneurial spirit and a sense of self-confidence in facing challenges in entrepreneurship. The entrepreneurship can help increase self-confidence in children by directly involving them in the family business. In this way, they can grow the confidence and intention of social entrepreneurship so that they are better prepared to become successors to the family business in the future.